2020
DOI: 10.1136/bmjopen-2020-037646
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in complete childhood immunisation in Nepal: results from a population-based cross-sectional study

Abstract: ObjectiveTo investigate the effect of different aspects of inequality on childhood immunisation rates in Nepal. The study hypothesised that social inequality factors (eg, gender of a child, age of mother, caste/ethnic affiliation, mother’s socioeconomic status, place of residence and other structural barrier factors such as living in extreme poverty and distance to health facility) affect the likelihood of children being immunised.DesignUsing gender of a child, age of mother, caste/ethnic affiliation, mother’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 19 publications
3
27
0
3
Order By: Relevance
“…This suggests that individuals in the poorest subpopulations are 27% (95%CI [16%,37%]) less likely to be fully vaccinated than those in the richest. This result is consistent across the vast majority of included studies and datasets, only Nepal, the Gambia, China, and Brazil have studies suggesting a negative influence or no significant trend [86, 50, 46, 48, 52]. We do note some variation over time in Ethiopia and China.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This suggests that individuals in the poorest subpopulations are 27% (95%CI [16%,37%]) less likely to be fully vaccinated than those in the richest. This result is consistent across the vast majority of included studies and datasets, only Nepal, the Gambia, China, and Brazil have studies suggesting a negative influence or no significant trend [86, 50, 46, 48, 52]. We do note some variation over time in Ethiopia and China.…”
Section: Resultssupporting
confidence: 86%
“…Wuneh et al, however, found no differences by wealth in rural Ethiopia [116]. In Nepal, Pakistan, and Tanzania, associations in the disparity of vaccination coverage among wealth quintiles was found to change over time, with Nepal and Pakistan displaying a decreasing disparity and Tanzania showing increases [85, 86, 87, 82, 117, 118, 83, 104]. In Vietnam and Thailand, studies found conflicting associations with immunisation and wealth [93, 119, 25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, geographically Province 2 is easily accessible, the lower vaccination coverage could be due to low literacy rate, hesitancy towards vaccination, knowledge and attitude about the immunization program, lack of proper health care infrastructure in rural areas, and other cultural barriers. [39][40][41] In case of Province 6 the lower age appropriate coverage could be due to hard to reach terrain, lack of awareness about the immunization schedule, lack of su cient infrastructure such as transportation and storage facilities, and lack of human resource in health sector. 32,33 Province 3 had the highest coverage of almost all the vaccines as it is the central region with most of the areas urbanized and developed.…”
Section: Discussionmentioning
confidence: 99%
“…Access to COVID-19 vaccines comes on the back of existing general vaccine access challenges, particularly for the most at-risk populations in LMICs. In Nepal, equity gaps in childhood immunisation coverage have narrowed over time, but there are still substantial inequalities, by household wealth, maternal education, ethnic group and region 18,19 . Indonesia is among 20 countries prioritised by the Global Vaccine Alliance (GAVI), facing severe challenges related to coverage, equity and sustainability of routine immunization 20 .…”
Section: Vaccination Access and Acceptancementioning
confidence: 99%